Penyelenggaraan Tertib Administrasi Bidang Pertanahan Untuk Menunjang Pelaksanaan Kewenangan, Tugas dan Fungsi i Badan Pertanahan Nasional - Mira Novana Ardani (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract Based on MPR Decree No.IV / MPR / 1978, a policy on land affairs, known as the chess discipline in the land sector, was published in Presidential Decree Number 7 of 1979, one of which included land administration discipline. How to conduct an orderly administration of land affairs to support the implementation of the authorities, duties, and functions of the National Land Agency. This study uses normative juridical methods. Administration of Land Affairs to support the implementation of the authority, duties, and functions of the National Land Agency by using a computerized system of land activities, which is an electronic system. Keywords: Administrative order, Land Affairs, National Land Agency AbstrakAtas dasar Tap MPR No.IV/MPR/1978, dikeluarkan kebijaksanaan bidang pertanahan yang dikenal dengan catur tertib bidang pertanahan sebagaimana dimuat dalam Keppres Nomor 7 Tahun 1979, salah satunya meliputi tertib administrasi pertanahan. Bagaimana cara menyelenggarakan tertib administrasi bidang pertanahan untuk menunjang pelaksanaan kewenangan, tugas, dan fungsi Badan Pertanahan Nasional. Penelitian ini menggunakan metode yuridis normatif. Penyelenggaraan Tertib Administrasi Bidang Pertanahan untuk menunjang pelaksanaan kewenangan, tugas, dan fungsi Badan Pertanahan Nasional dengan cara menggunakan sistem komputerisasi kegiatan pertanahan yang merupakan sistem elektronik. Kata kunci: Tertib administrasi, Pertanahan, Badan Pertanahan Nasional